Influenza antiviral treatment in spinal cord injury patients, 2007–2010. (January 2015) - Evans, Charlesnika T.; Rogers, Thea J.; Goldstein, Barry; Weaver, Frances M.; LaVela, Sherri L.
Abstract : Objective: This study assessed antiviral medication use for treatment of influenza-like illness (ILI) in Veterans with spinal cord injury or disorder (SCI/D) and examined whether antiviral prescribing improved over time. Design: Retrospective cohort study of Department of Veterans Affairs (VA) facilities. Participants: Veterans with SCI/D and matched non-SCI/D controls (matched by facility and date of visit/admission) who were diagnosed by a clinician with ILI during the period 1 October 2007 to 31 May 2010. Main outcome measures: Antiviral receipt and appropriateness were examined. Appropriate antiviral prescribing was defined as patients who received an antiviral medication within 2 days of collection of a sample for diagnostic testing or within 2 days of symptom onset. Results: We identified 101 influenza visits/admissions for veterans with SCI/D and 123 for controls. Antiviral prescribing for Veterans with SCI/D increased from 37.1% in 2007/2008 to 67.6% in 2009/2010 (P = 0.01) and appropriate antiviral prescribing increased from 20.0 to 41.2% (P = 0.05). Predictors of antiviral prescribing included being treated in the 2009/2010 influenza season (vs. 2007/2008) and having a cough. Fever, aches/myalgia, or a positive influenza test was associated with appropriate antiviral treatment. SCI/D was an independent predictor of receiving antiviral treatment (adjusted odds ratio = 1.16, 95% confidence interval 1.04–1.29), but having SCI/D was not associated with receiving appropriate treatment. Conclusions: Influenza antiviral prescribing increased over time and in a larger proportion in veterans with SCI/D (vs. controls). This suggests that providers treating patients with SCI/D recognize treatment guidelines and their importance in a high-risk population. Continued efforts are needed to improve appropriate influenza antiviral prescribing.